Case authoring from text and historical experiences - Zaluski, Marvin (University of Ottawa (Canada), 2003)
Knowledge management is the acquisition and distribution of knowledge within organizations. The knowledge acquisition bottleneck problem is an obstacle in implementing knowledge management system. This thesis describes a solution to this problem through a semi-automated approach that sorts through the mass of information that is available within the organization. Our tool was developed using state-of-the-art Case-Based Reasoning and Information Extraction technologies. More specifically, we developed a semi-automated case authoring method that creates a case-base in two steps. It begins by extracting knowledge from readily available resources such as technical documents and follows by complementing those cases using individual experiences in the organization. The case-base developed is a reflection of the knowledge encoded in the technical documentation and an authentication of the cases with real historical instances. Our case authoring approach is applied to the real world in the aerospace domain.
Keywords: Computer Science.